2019
DOI: 10.3389/fphys.2019.00761
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Functional Brain Connectivity After Long-Duration Spaceflight as Revealed by fMRI

Abstract: The present study reports alterations of task-based functional brain connectivity in a group of 11 cosmonauts after a long-duration spaceflight, compared to a healthy control group not involved in the space program. To elicit the postural and locomotor sensorimotor mechanisms that are usually most significantly impaired when space travelers return to Earth, a plantar stimulation paradigm was used in a block design fMRI study. The motor control system activated by the plantar stimulation involved the pre-centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 119 publications
(187 reference statements)
1
58
1
Order By: Relevance
“…The few studies that previously have found signs of functional neuroplasticity after spaceflight have often observed changes in the activity of or connectivity with the cerebellum and primary motor cortex, although these changes have not yet been noted in the basal ganglia ( 10 , 11 ). In addition, one previous study has used dMRI to investigate changes in the brain as a result of long-duration spaceflight, and they found fractional anisotropy decreases in the cerebellum, which the authors ascribe to disrupted WM structural connectivity ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The few studies that previously have found signs of functional neuroplasticity after spaceflight have often observed changes in the activity of or connectivity with the cerebellum and primary motor cortex, although these changes have not yet been noted in the basal ganglia ( 10 , 11 ). In addition, one previous study has used dMRI to investigate changes in the brain as a result of long-duration spaceflight, and they found fractional anisotropy decreases in the cerebellum, which the authors ascribe to disrupted WM structural connectivity ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…past work investigating vestibular processing in astronauts. Two previous studies suggest changes from pre-to postspaceflight in resting-state (Demertzi et al, 2016) and taskbased connectivity (Pechenkova et al, 2019) in brain networks that support vestibular function. Our past work has identified disrupted white matter structural connectivity in several tracts that underlie sensory integration and vestibular processes and associations of these brain changes with balance declines (Lee et al, 2019b).…”
Section: Extent (K)mentioning
confidence: 97%
“…Astronauts also present with decreased skin sensitivity on the soles of the feet following spaceflight (Lowrey et al, 2014), which has been attributed to in-flight sensory reweighting (i.e., the process of adjusting the magnitude of different sensory contributions to motor control) (Assländer and Peterka, 2014) in compensation for unreliable vestibular inputs in microgravity. A single-subject case study (Demertzi et al, 2016) and recent study of 11 cosmonauts (Pechenkova et al, 2019) examining resting-state and task-based functional magnetic resonance imaging (fMRI) connectivity found evidence for vestibular cortex reorganization and multisensory reweighting following longduration spaceflight. This work provides preliminary evidence of flight-related central vestibular plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Transient experimental vestibular deprivation has been shown to elicit (a) changes in the functional connectivity of the right supramarginal gyrus (SMG) of cosmonauts (Pechenkova et al, ) which correlated with the severity of motion sickness and (b) altered responsivity in the vestibular cortical network (Yuan et al, ). Prolonged head‐down‐tilt bed rest over >2 months (HDBR) is utilized as a spaceflight analog research condition to study related behavioral and neural changes in the absence of gravitational modifications (Yuan et al, ).…”
Section: Introductionmentioning
confidence: 99%